2019
DOI: 10.5897/ijbc2019.1294
|View full text |Cite
|
Sign up to set email alerts
|

Current distribution, regeneration and management practice of Hagenia abyssinica in different agroforestry systems of Ethiopia: A review

Abstract: Hagenia abyssinica is a multipurpose tree, which is sparsely distributed in the highland of Ethiopia. It is used for illness remedy, furniture, fuel, and as a soil additive. This review provides information on the present status and management practice of H. abyssinica in Ethiopia to give urgency care other than that given to introduced species for future conservation. The foliage and flowers have a higher quality of N and P for managing soil fertility. However, market availability is diminished. Its healing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…However, the species tended to decrease as the altitudes were getting to the peak, which is probably due to poor edaphic factors Moreover, the tendency of species displaying linear pattern adjacent rivers may indicate that these plants require high soil moisture content and that in drier areas these species survival could be uncertain. These findings relate to those reported by [38] who associated the growth of Hagenia abyssinica with fertile and moist soils. Also, similar findings are reported in studies conducted in Ethiopia which confirm that Myrica salicifolia was found to be highly threatened by prolonged drought although other factors including anthropogenic activities contributed as well [6] [36].…”
Section: Discussionsupporting
confidence: 89%
“…However, the species tended to decrease as the altitudes were getting to the peak, which is probably due to poor edaphic factors Moreover, the tendency of species displaying linear pattern adjacent rivers may indicate that these plants require high soil moisture content and that in drier areas these species survival could be uncertain. These findings relate to those reported by [38] who associated the growth of Hagenia abyssinica with fertile and moist soils. Also, similar findings are reported in studies conducted in Ethiopia which confirm that Myrica salicifolia was found to be highly threatened by prolonged drought although other factors including anthropogenic activities contributed as well [6] [36].…”
Section: Discussionsupporting
confidence: 89%